Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian pada Restoran Modern dan Tradisional - Acep Samsudin; Rusdi Hidayat; Indy Melva Adinda Marsha; Nabiilah Shinta Ramadhani; Cantika Aura Jahzy; Muhammad Galih Wijaya (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
In modern times like today, people have two options for choosing food, namely fast food that can be purchased at modern restaurants and regional specialties that can be purchased at traditional restaurants. The research in this journal aims to find various factors that influence people's decisions in purchasing food at modern and traditional restaurants. The research method used in this research is the study of literature and literature. The results show that consumer purchasing decisions are influenced by actual and ideal state, affection factors, consumer satisfaction factors with products, and social factors. Keywords: Modern Restaurant, Traditional Restaurant, Purchase Decision Factors.